Coulomb-explosion imaging of concurrent CH2BrI photodissociation dynamics - Burt, Michael; Boll, Rebecca; Lee, Jason W. L.; Amini, Kasra; Köckert, Hansjochen; Vallance, Claire; Gentleman, Alexander S.; Mackenzie, Stuart R.; Bari, Sadia; Bomme, Cédric; Düsterer, Stefan; Erk, Benjamin; et al. (My University, 2017)
The dynamics following laser-induced molecular photodissociation of gas-phase CH2BrI at 271.6 nm were investigated by time-resolved Coulomb-explosion imaging using intense near-IR femtosecond laser pulses. The observed delay-dependent photofragment momenta reveal that CH2BrI undergoes C-I cleavage, depositing 65.6% of the available energy into internal product states, and that absorption of a second UV photon breaks the C-Br bond of CH2Br. Simulations confirm that this mechanism is consistent with previous data recorded at 248 nm, demonstrating the sensitivity of Coulomb-explosion imaging as a real-time probe of chemical dynamics.